Desenvolvimento de mecanismo sulcador associado ao processo de semeadura e características agronômicas em função do método de semeadura e velocidade - Amorim, Marcelo Queiroz (2017)
The Brazilian semiarid can be characterized by irregular rainfall in time and space, evapotranspirometric rates high, shallow soils with low fertility and water retention capacity, being necessary methods adequacy to water retention in the soil. In all methods of the tillage to rainwater captation in situ the seeding is realized in moment distinct tillage. The objective of this study was to evaluate the energy and operational performance of the tractor-seed equipped with furrow mechanics, evaluation sowing quality, formation of the ridge and sowing in a single operation, cultural with performanceand soil physical attributes and maize productivity as a function of two sowing sites and three speeds in the Northeast region. The experiment was installed at the Federal University of Ceará, Pici Campus. For the energetic and operational performance, quality sowing process and cultural evaluation of maize, the experimental in factorial design(2x3) + 3, two sowing sites (above the ridge and inside the groove), three speeds (5.5, 7.5 and 9.5 km h -1 ) and three controls (conventional sowing at speeds 5.5, 7.5 and 9.5 km h-1 ), with four replications. For the physical attribute of the soil, the experimental was factorial design (2x2x3), two site sowing (above the ridge and inside the groove), two periods (15 and120 days after sowing) and three speeds (5.5, 7.5 and 9.5 km h-1 , with four replications. The data of energy and operational performance, sowing quality, crop production and soil physical attributes were submitted to analysis of variance and to the means test. In the factorial comparison with the controls, the Dunnet test (p<0.05) was used. For process quality formation groove-ridge the data was evaluation of the Statistical Control Quality (SCQ). The seeding within the furrow presented better energy and operational performance, and higher corn productivity was observed for sowing on top of the ridge.